Memory of social experience affects female fecundity via perception of fly deposits - E. K. Fowler; S. Leigh; W. G. Rostant; A. Thomas; A. Bretman; T. Chapman (BMC Biology, 2022)
Abstract Background Animals can exhibit remarkable reproductive plasticity in response  to their social surroundings, with profound fitness consequences. The presence of same-sex conspecifics can signal current or future expected competition for resources or mates. Plastic responses to elevated sexual competition caused by exposure to same-sex individuals have been well-studied in males. However, much less is known about such plastic responses in females, whether this represents sexual or resource competition, or if it leads to changes in investment in mating behaviour and/or reproduction. Here, we used Drosophila melanogaster to measure the impact of experimentally varying female exposure to other females prior to mating on fecundity before and after mating. We then deployed physical and genetic methods to manipulate the perception of different social cues and sensory pathways and reveal the potential mechanisms involved. Results The results showed that females maintained in social isolation prior to mating were significantly more likely to retain unfertilised eggs before mating, but to show the opposite and lay significantly more fertilised eggs in the 24h after mating. More than 48h of exposure to other females was necessary for this social memory response to be expressed. Neither olfactory nor visual cues were involved in mediating fecundity plasticity—instead, the relevant cues were perceived through direct contact with the non-egg deposits left behind by other females. Conclusions The results demonstrate that females show reproductive plasticity in response to their social surroundings and can carry this memory of their social experience forward through mating. Comparisons of our results with previous work show that the nature of female plastic reproductive responses and the cues they use differ markedly from those of males. The results emphasise the deep divergence in how each sex realises its reproductive success.